PROFIL KELUARGA DISFUNGSIONAL PADA PENYANDANG MASALAH SOSIAL DI KOTA SEMARANG - Indrawati, Endang Sri; Hyoscyamina, Darosy Endah; Qonitatin, Novi; Abidin, Zaenal (Jurnal Psikologi, 2014)
AbstractDysfunctional family is a social problem that also caused other social problems. It is important to understand the basic character of family which has social problem in order to prevent and to solve social problems. This study aims to describe the profile of dysfunctional families which have social problems. The subject comprised 92 persons (70 men; 22 women; aged 15-79 years) who have social problems and stayed in the social centers, social rehabilitation centers, or slum areas of Semarang city. Data were collected using Dysfunctional Family Questionnaire and Risk-Parenting Scale and were analyzed using descriptive statistics. The results showed that the majority (51.09%) of dysfunctional families which have social problems come from low economic status, low level of educational background (21.74% fathers and 14.13% mothers finished junior high school of higher; the remaining subject went to elementary school or were illiterate); the majority of participants (69.56%) have more than three siblings. Among parental inadequate behaviors, smoking behavior was considered to bring strongly negative impact to the family members.